The Roger T. Sermon Community Center, Kansas City, Missouri - Midgley Shaughnessy Fickel; Scott Architects Inc. (Oz, 1982)
The Sermon Center has a long history of change. The original building was erected as the Dodgion Street Power Plant in 1902. Extensive changes were made in the 1920's, with new west and south facades graced by tall arched windows and pilasters…